KEPRIBADIAN TANGGUH (HARDINESS) PADA PEREMPUAN PENDERITA PASCA STROKE - Magdalena Anneke Smith; Hafsah Budi Argiati (JURNAL SPIRITS, 2013)
ABSTRACTThe purpose of the study is to investigate the hardy personality of pasca stroke sufferer. Hardiness was first described by Kobasa (1979) as a cognitive appraisal processes composed of three characteristics: challenge, commitment, and control. There were 4 women participants who stroke sufferer during 0-6 years. Results indicate hardiness of pasca stroke sufferer we able look at their behaviour. They still giving interest to do something are relate environment and another people. Beside that, support from family is material, morality, and information could be helping subject to appear the hardy personality. Defended good relationship with another people was method of subject to increase hardiness. Key words : commitment, control, challenge.